2021
DOI: 10.1057/s41269-021-00209-4
|View full text |Cite
|
Sign up to set email alerts
|

More competent thus more legitimate? MPs’ discourses on deliberative mini-publics

Abstract: MPs face a dilemma when it comes to deliberative mini-publics (DMPs): in a context of distrust they may see it as an opportunity to re-legitimize themselves and solve complex policy issues. But it could also challenge the quasi-monopoly they used to have on political decisions and undermine the role of the Parliament and the primacy of elections. The article is founded on 91 face-to-face interviews with French-speaking Belgian MPs sitting in federal or regional parliaments. First, we describe the profile of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…2. Nevertheless, the deliberative processes (with randomly selected participants) are less current in the Dutch speaking community (Vrydagh et al 2020;Rangoni, Bedock, and Talukder 2021). 3.…”
Section: Notesmentioning
confidence: 99%
“…2. Nevertheless, the deliberative processes (with randomly selected participants) are less current in the Dutch speaking community (Vrydagh et al 2020;Rangoni, Bedock, and Talukder 2021). 3.…”
Section: Notesmentioning
confidence: 99%
“…For instance, participatory budgeting processes are mainly created by left‐wing local coalitions (Sintomer et al., 2016). The same ideological pattern also appears in support for the principle of a randomly selected legislative assembly (Jacquet et al., 2020) as well as mini‐publics (Rangoni et al., 2021). In the same vein, in a large survey with local European councillors, Heinelt (2012) found that left‐wing and female councillors are more in favour of participatory reforms than the others.…”
Section: State Of the Art: Political Leaders And Citizens’ Assembliesmentioning
confidence: 75%
“…Second, some studies explore what political leaders expect from public participation in very general terms (Beswick & Elstub, 2019; Hendriks & Lees‐Marshment, 2019; Rangoni et al., 2021). Hendriks and Lees‐Marshment (2019) found that political leaders value the principle of public participation to collect information, connect with real people, check the feasibility of new policies and aid policy implementation.…”
Section: State Of the Art: Political Leaders And Citizens’ Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several empirical studies investigate the support of the broader population for the concept of minipublics in general (e.g., Pilet et al, 2020;Germann et al, 2021) and for specific instances (e.g., Devillers et al, 2021;Pow, 2021). Scholars also survey how decision-and policymakers conceive the functions of minipublics (Beswick and Elstub, 2019;Bobbio, 2019;Rangoni et al, 2021) and participatory processes (Dean, 2019;Hendriks and Lees-Marshment, 2019), their support for minipublics (Jacquet et al, 2020;Koskimaa and Rapeli, 2020) and their motivations to institutionalize them (Macq and Jacquet, 2021). Some of these studies analyze decision-makers' attitudes regarding a specific case, such as the Belgian Ostbelgien-model (Macq and Jacquet, 2021) or a minipublic in a parliamentary committee in the UK (Beswick and Elstub, 2019), while the others surveyed the perceptions about more general and abstract conceptions of minipublics-in particular the authority they should have- (Jacquet et al, 2020;Koskimaa and Rapeli, 2020;Rangoni et al, 2021) and broader processes of participatory governance and public engagement (Dean, 2019;Hendriks and Lees-Marshment, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%